(untitled) (Research, Society and Development, 2024)
Objective: To identify the role of prenatal care in preventing obstetric violence in pregnant and postpartum women. Methods: This is an integrative literature review, data collection was carried out in December 2023 in four databases, namely: PubMed, LILACS, BDENF and SciELO. Primary studies related to prenatal care as a means of preventing obstetric violence in pregnant and postpartum women, written in Portuguese, English and Spanish, were included. Results: The search resulted in 9 articles suitable for the review inclusion criteria, which were concentrated in the LILACS database (55.56%), followed by BDENF (22.22%) and PubMed (22.22%). Actions were identified to prevent obstetric violence by nurses in primary care regarding the perception and knowledge of forms of obstetric violence and guidance on women’s rights in prenatal care, childbirth and postpartum. Conclusion: It is concluded that humanized and qualified prenatal care plays a significant role in preventing obstetric violence, allowing the empowerment of pregnant women regarding physiological birth care and their rights in pregnancy-puerperal care.